Toby's story - Cameron, W. Bruce (Cameron, W. Bruce. Dog's purpose puppy tale., 2019)
Toby, an unusually calm beagle puppy, finds his purpose when Mona and her mother adopt him and teach him to be a therapy dog at a nursing home.